Nanoindentation and Deformation of Multilayered Au/Cu Films. Issue 1 (2nd January 2017) - Fan, Yu-Cheng; Fang, Te-Hua; Lin, Kuan-Ming; Qiu, Ren-Zheng
Abstract: The mechanical properties of single and multilayer gold and copper films are studied using molecular dynamics and deformation, the slip effect, the load bearing capacity and energy differences are also discussed. Results showed that as the indentation depth increases in a multilayer model, the grain boundaries of the first layer are broken and the atoms diffuse into the lower layer, thereby leading the change of the amount of slip. Single-crystal Au and Cu models generate more slippage due to lower bond energy between atoms. The larger the amount of atomic flow under indentation is, the larger the amount of slip is. As the depth of the indentation increases, the area influenced by indentation increases and the maximum load bearing capacity and potential energy also increase. Plastic deformation from indentation at high speed does not result from dislocation slip, but from a larger force that destroys the bonds between atoms. At higher temperature, the amount of slip around the indenter is less obvious and the structure is gradually softened. Moreover, the same depth of indentation can be achieved with a smaller load force for higher temperature. Abstract :